Analysis of Social Media User Responses to Verbal Violence in the Cyber World - Moulita; Debora, Chintya; Nik Hasan, Nik Norma (Fakultas Dakwah UIN Saizu Purwokerto, 2024)
Violence on social media comes in various forms, one of which is verbal, such as rude or hateful comments, threats, or insults. This research will provide an overview of the responses of social media users to the verbal violence they experience in cyberspace. Researchers conducted interviews with five informants aged 19 – 21 years who had experienced violence on social media. Apart from that, researchers also completed the data by conducting interviews with expert informants in media literacy. The research results showed that all informants received indirect types of verbal violence through their social media in the form of teasing and body shaming, both from friends and strangers. Specifically, some informants experienced direct and indirect verbal violence, as well as repressive violence. The responses of the informants in responding to verbal violence were at the attitude and behavior level, including remaining silent because they felt like they were in the minority and did not need to reply, hiding their stories or status on social media from the perpetrator, and even contacting the perpetrator to get an explanation. Expert informants assess that violent behavior that appears in the media is caused, among other things, by the various backgrounds of media users, both in terms of economic education and literacy levels. Many responses or ways can be made in responding to online violence, but according to expert informants, the ideal way is to provide an answer or warning politely. It also aims to educate fellow media users.